Pelatihan Literasi Media Berbasis Digital Marketing Pada Masyarakat Link. Sambi Gerowong, Kelurahan Sukawana, Serang-Banten - Islami, Fahma; Muhibuddin; Tb. Nur Wahyu; Ikrima; Moch. Hasbi Ashshidiqie (AdZikra : Jurnal Komunikasi & Penyiaran Islam, 2025)
This community service activity was conducted at Link. Sambi Gerowong, Sukawana Village in Serang District, Serang City, Banten. This training aims to provide digital literacy training, both digital transformation, technological transformation and digital marketing, to raise awareness of the community towards the current era of digitalization, which is increasingly rapid and advanced, so that today's society needs this awareness to facilitate digital development and application in a prosperous life. The results of the activity showed a significant development, both in terms of theoretical knowledge and practical skills. Recommendations were also made to extend similar programs to other villages to broaden the impact of digitalization in the modern era, to invite village youth to become drivers of the community's digital transformation, and to provide shared workspaces with Internet access as digital training and production centers.